The Human Caliphate: An Analysis of Gender Equality between Men and Women - Muhammad Saukani; Khairul Fuadi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Man is a perfect being created by the Lord as a filling and casting agent to accomplish the task which he has been given. Human beings as caliph are so often misunderstood by most people. Most people misinterpret the concept of human caliph itself, assuming that man as a caliph is directed toward men as a woman. Such efficiency would certainly violate the very definition of caliphate. Since the qur 'an and the mufastors were clearly not claimed that the caliph was directed to men only. We reflect to the qur 'an that in every verse it is mentioned, there is no reference to caliph towards men only, because all the caliph words that are in general meaning, do not point to a single gender. From here it must be understood, that human beings as caliph are addressed to all male and female sexes. Because humans are defined by men and women. There's no text that humans are just men. It is this understanding that needs to be clarified and explained, as in this infamy will provide a description that man as the caliph is addressed to men and women.